2016
DOI: 10.1002/eji.201646359
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells induce tolerance predominantly by cargoing antigen to lymph nodes

Abstract: Plasmacytoid dendritic cells (pDCs) have been shown to induce tolerance to innocuous antigens. Their migratory properties allow them to take up antigens from the periphery and transport them to the draining lymph nodes or to the thymus. However, pDC‐T‐cell interaction in the primary and secondary lymphoid organs still remains poorly defined. In this study, we show that resting pDCs loaded with exogenous antigen could induce tolerance when transferred intralymphatically into a single lymph node of wild‐type C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…110 ). 112,113 In addition, DCs can rapidly mature from circulating monocytes recruited during injury and inflammation, and distinguishing monocyte-derived DCs and tissue-resident DCs can be a challenge, particularly in humans. 111 The cDC1s are specialized to sample antigen from the alveolar space, but all DC subsets, including pDCs, are able to transport antigen to draining lymph nodes.…”
Section: Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…110 ). 112,113 In addition, DCs can rapidly mature from circulating monocytes recruited during injury and inflammation, and distinguishing monocyte-derived DCs and tissue-resident DCs can be a challenge, particularly in humans. 111 The cDC1s are specialized to sample antigen from the alveolar space, but all DC subsets, including pDCs, are able to transport antigen to draining lymph nodes.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…111 The cDC1s are specialized to sample antigen from the alveolar space, but all DC subsets, including pDCs, are able to transport antigen to draining lymph nodes. 112,113 In addition, DCs can rapidly mature from circulating monocytes recruited during injury and inflammation, and distinguishing monocyte-derived DCs and tissue-resident DCs can be a challenge, particularly in humans. 16,114 It is also important to note that the nomenclature can be confusing because definitions have varied over time, and the terms cDC and myeloid DC are used to describe the same cells.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Clinical research has shown that IL-2 therapy is effective in promoting tolerance in autoimmune and inflammatory conditions, primarily by enhancing the development and maintenance of regulatory T cells 18 . In this study, we additionally report that an increase in plasmacytoid DCs, also known for their tolerogenic immune properties against innocuous antigens 19,20 , to be unique to infants with PST. These cells may play a central role in averting clinical allergy in the presence of allergen-sIgE.…”
Section: Resultsmentioning
confidence: 52%
“…In the steady state, pDCs express very low levels of MHC-II and costimulatory molecules and may contribute to T cell unresponsiveness. Though pDCs are not as efficient as cDCs for antigen presentation to T cells, pDCs can upregulate MHC-II molecules on their surface and migrate to the T cell area, induce T cell proliferation and Treg generation (93, 94). Activated pDCs can have enhanced MHC-II expression (95, 96), allowing for prolonged T cell activation that may contribute to Treg development as increased MHC-II on pDCs is required for Treg homeostasis (97).…”
Section: Dc-mediated Peripheral Tolerance Mechanismsmentioning
confidence: 99%